Outcome-Based English Learning for Islamic Economics Students in Indonesian Universities - Rahman, Muthia; Syafitri, Widya; Laila, Yulia; Febrina, Reni; Widianita, Rika (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
This study addresses the need for Islamic Economics graduates to acquire not only theoretical knowledge but also practical English communication skills, in order to meet the challenges of global economic integration and the Islamic finance industry. The research aims to redesign English for Economics courses by applying principles of Outcome-Based Education (OBE). Using a qualitative descriptive design, this study analyzes curriculum documents, previous research, and case examples from Islamic universities to examine the integration of communicative competence, critical thinking, and contextual understanding into course design. The findings indicate that OBE-based instruction enhances students’ linguistic proficiency, professional readiness, and international engagement by aligning learning outcomes with industry requirements. The study contributes to curriculum development by offering a framework for implementing OBE in English for Islamic Economics. Its novelty lies in positioning OBE as a strategic approach to bridge the gap between traditional reading-focused instruction and the real-world communicative demands of Islamic economics education.